Rehabilitation Program for Postlaryngectomy Patients Following Ileocolon Flap Transfer for Voice Reconstruction: An Essential Part of Success - Lin, Kai-Yuan Katie; Huang, Chi-wen; Chen, Shih-Heng; Lee, Jian-Jr; Chen, Hung-chi (Journal of Reconstructive Microsurgery, 2024)
Background Speech restoration is important for communication and social activities after pharyngolaryngectomy in head and neck cancer or corrosive injury. Several techniques of voice restoration have been developed to improve life quality. The aim of this paper was to focus on the microsurgical transfer of ileocolon flap and outcome of further voice rehabilitation.Patients and Methods From 2010 to 2022, 69 patients had ileocolon flap at our hospital with postoperative speech training and regular follow-up for over 1 year. The patients received deglutition training first, followed by voice rehabilitation. Voice outcomes were evaluated at an interval of 3 months and finally at 12 months of voice training rehabilitation. Among other examinations, the speech function was evaluated using a 4-point Likert scale and senior surgeon (H-c.C.) scoring system.Results The results showed that speech function reached 13.1% of excellent voice, 65.1% of good voice, 13.1% of fair result, and 8.7% of poor result by Likert scales. Meanwhile, the senior surgeon (H-c.C.) score showed 17.4% of excellent, 63.8% of moderate, and 18.8% of poor results. About voice laboratory results, maximal phonation time was 11.0 seconds, and the average number counted in one breath was 15. Loudness and frequency showed 56.0 dB and 105.0 Hz, respectively.Conclusion The study showed that after voice reconstruction with ileocolon flap followed by the voice rehabilitation program, the patients would have a better understanding of the altered anatomical structures and practice in a more efficient way. Adequate recommendation by the therapists to plastic surgeons for revision surgeries optimized voice function of the patients.
Keywords: ileocolon flap; laryngectomy; rehabilitation; voice reconstruction